Socioeconomic health and impact of sickle cell disease and vaso-occlusive crises in India: results from B-VOCAL study - Dipty Jain; Ravindra Kumar; Nandakumar Menon; Disha Shetty; Tulika Seth; Shashank Udupi; Suman Jain; Seema Bhatwadekar; Rabindra Jena; Bharat Parmar; Anil Goel; Ashvin Vasava; et al. (BMJ Global Health)
Background Sickle cell disease (SCD) with vaso-occlusive pain crisis (VOC) has a major impact on healthcare resource utilisation and poses a significant financial burden for the patients. This study examines the economic implications of managing VOC in individuals with SCD in India, from the perspectives of patients, healthcare system and society.Methods This cross-sectional, observational study included 1000 patients with SCD across 14 centres enrolled from November 2021 to June 2022. Data were collected systematically using a structured electronic case record form. Employing a cost-of-illness approach, the study assessed the economic impact of SCD and VOC management, including assessing patient/caregiver costs, healthcare provider costs and societal burdens extrapolated to the larger SCD population in India.Findings Patients incurred substantial out-of-pocket expenses, with a median (IQR) annual expenditure of INR 22 080/US$267 (IQR: INR 36 990/US$447.7), representing 14.65% (26.53) of their annual household income. Overall, catastrophic healthcare expenditure (CHE) for total annual average SCD care with VOC management was experienced by 624 patients (62.40%). Moreover, 334 patients (33.4%) experienced CHE of >25% of the annual household income. Patients with SCD with VOC had significantly higher median annual healthcare expenditures and used a higher median percentage of their yearly household income on healthcare compared with those without VOC (19.82% vs 6.08%; p<0.001). Cost incurred by healthcare providers for VOC management in different healthcare facilities (outpatient department/emergency department/intensive care unit) was similar across different reimbursed facilities (government tertiary care hospitals, non-governmental organisation-operated healthcare centres and government-subsidised healthcare setups). The estimated societal burden for VOC management in 1 year for 1000 patients visiting different healthcare facilities was around INR 35 119 074 (~US$0.42 million).Interpretation These findings highlight the considerable economic strain on both patients and healthcare providers in SCD and VOC management, which is similar to the other non-communicable diseases emphasising the urgent need for targeted interventions to improve financial hardships among patients.Funding The study was funded by Novartis Healthcare Private Limited.